Risk factors of zoonotic diseases transmitted by animals in consulting room and veterinary clinics (Revista Sistemas de Producción Agroecológicos, 2015)
The work in consulting room and veterinary clinics, although not involving the deliberate intention to manipulate biological agents, may give rise to exposure to these agents, because there is direct contact with animals, which may be sick or be carriers of pathogens, or remove it in their different biological fluids; in this article is described the main risk factors from exposure to biological agents and its relation to zoonoses in consulting room and veterinary clinics, where their most attention is focused is on the canine and feline species as main pets.
Keywords: zoonoses; infectious agents; prevention